New Avenues for Phosphodiesterase Inhibitors in Asthma - Matera MG; Ora J; Cavalli F; Rogliani P; Cazzola M (Dove Medical Press, 2021)
Maria Gabriella Matera,1 Josuel Ora,2 Francesco Cavalli,2 Paola Rogliani,2,3 Mario Cazzola3 1Department of Experimental Medicine, University of Campania “Luigi Vanvitelli”, Naples, Italy; 2Respiratory Diseases Unit, “Tor Vergata” University Hospital, Rome, Italy; 3Department of Experimental Medicine, University of Rome “Tor Vergata”, Rome, ItalyCorrespondence: Mario CazzolaDipartimento di Medicina Sperimentale, Università di Roma Tor Vergata, Rome, ItalyEmail mario.cazzola@uniroma2.itIntroduction: Phosphodiesterases (PDEs) are isoenzymes ubiquitously expressed in the lungs where they catalyse cyclic adenosine monophosphate (cAMP) and cyclic guanosine monophosphate (GMP), which are fundamental second messengers in asthma, thereby regulating the intracellular concentrations of these cyclic nucleotides, their signaling pathways and, consequently, myriad biological responses. The superfamily of PDEs is composed of 11 families with a distinct substrate specificity, molecular structure and subcellular localization. Experimental studies indicate a possible role in asthma mainly for PDE3, PDE4, PDE5 and PDE7. Consequently, drugs that inhibit PDEs may offer novel therapeutic options for the treatment of this disease.Areas Covered: In this article, we describe the progress made in recent years regarding the possibility of using PDE inhibitors in the treatment of asthma.Expert Opinion: Many data indicate the potential benefits of PDE inhibitors as an add-on treatment especially in severe asthma due to their bronchodilator and/or anti-inflammatory activity, but no compound has yet reached the market as asthma treatment mainly because of their limited tolerability. Therefore, there is a growing interest in developing new PDE inhibitors with an improved safety profile. In particular, the research is focused on the development of drugs capable of interacting simultaneously with different PDEs, or to be administered by inhalation. CHF 6001 and RPL554 are the only molecules that currently are under clinical development but there are several new agents with interesting pharmacological profiles. It will be stimulating to assess the impact of such agents on individual treatable traits in specially designed studies.Keywords: asthma, phosphodiesterases, phosphodiesterase inhibitors, bifunctional drugs, treatable traits therapeutic approach